Studi Kritis Bahan Ajar PABP Materi Gibah dan Tabayun di Kelas 7 SMPIT Takhassus Al-Qur’an Ashabiq Sukabumi - Ressy Resviati Putri; Siti Qomariyah; Ai Siti Rahmawati; Lia Aliyah; Leni Sumarni (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to conduct a critical study of the teaching materials for Islamic Religious Education and Character Building (PABP), specifically on the material "Avoiding Backbiting and Carrying Out Tabayun" used in class VII of SMPIT Takhassus Al-Qur'an Ashabiq. The focus of the study in this study covers several important aspects, namely learning objectives, the material delivered, the learning methods and models applied, evaluation of learning outcomes, and sources and references for teaching materials used by teachers and students. The approach used in this study is descriptive qualitative with data collection techniques through document studies of teaching materials, observations of the learning process in the classroom, interviews with teachers and students, and data validation is carried out through expert audits to ensure the accuracy of the findings. The results show that the teaching materials used have referred to the principles of the Independent Curriculum and the Pancasila Student Profile, which emphasize the development of character and student competencies as a whole. However, several significant weaknesses were found, especially in terms of integration between learning objectives with learning activities and evaluations carried out. Learning materials are structured in a normative and idealistic manner, but they do not adequately accommodate students' real-life contexts, particularly in facing the challenges of today's digital era, which significantly impact how they understand and internalize religious values. Learning evaluation is still dominated by cognitive measures such as written tests and conceptual understanding, while the attitudinal and skill dimensions, which are crucial for character education, have not been optimally measured. Furthermore, the learning resources used are quite limited, relying solely on textbooks and student worksheets (LKS), without any support from contemporary literature or digital media that could enrich the learning process and make it more engaging and relevant to today's students.